Determination of Phytochemicals as Potential Inhibitors of Matrix Metalloproteinases (MMPs) with Special Reference to Breast Cancer - Roy, Anirban; Chakraborty, Indira; Banerji, Aniruddha (Issues and Development in Health Research Vol. 5, 2021)
Both in India as well as globally, breast cancer is the most common type of cancer in women. The major causes for mortality and poor clinical prognosis in most cancers including breast cancers is metastasis and secondary tumour formation and even with modern methods of treatment, metastasized cancers remain largely untreatable. The matrix metalloproteinases (MMPs), a family of zinc dependant endopeptidase enzymes, play critical roles in the regulation of metastasis and tumour development, making MMPs possible therapeutic targets for preventing metastasis. Treatment with phytochemical compounds has the potential to reduce side effects of treatment and make treatment more affordable. The objective of this article is to analyse the potential of four such phytochemicals resveratrol, theaflavin, curcumin and all-trans retinoic acid as MMP inhibitors with special reference to breast cancers.